One‐Pot Synthesis of Multicentric DIL@PDIL Catalyst for Mild CO 2 Conversion to Cyclic Carbonates - Wang, Yeying; Zeng, Yanbin; Tang, Zhenzhu; Qiu, Jiaxiang; Wang, Xiaoxia; Xie, Guanqun; Wang, Xiufang (Chemistry : a European journal, 2025)
Among the various studies on CO 2 utilization, the sustainable and cost‐effective fixation of CO 2 into cyclic carbonates remains one of the most intriguing subjects. To this end, a novel type of composite dicationic ionic liquid material, DIL@PDIL, was developed. This composite consists of a dicationic ionic liquid (DIL), DMAP[TMGH]Br, supported on a polymeric dicationic ionic liquid (PDIL), P‐DVB/Im[TMGH]Br. The multicentric high‐ion‐density material was prepared with exceptional efficiency from five readily available starting materials in one pot through simultaneous quaternization, neutralization and polymerization. The structure was characterized using FT‐IR, XPS, SEM, TGA, ICP‐MS and BET, as well as through stepwise synthesis verification. Evaluation of the catalytic performance revealed the ionic liquid composite delivered chloropropylene carbonate (CPC) in excellent yield and selectivity from either pure CO 2 or simulated flue gas at 60 °C and relatively lower pressure. Additionally, the DIL@PDIL catalyst exhibited good recyclability and were applicable to a range of epoxide substrates. The high activity of the the catalyst could be attributed to the abundant [TMGH] + hydrogen bonding donors and Br − anions, which synergistically catalyze the epoxide ring‐opening, as well as the abundant ‐COO − groups and imidazole cations, which facilitate the adsorption and activation of CO 2 .